Cumulative Evidence for Relationships Between 8q24 Variants and Prostate Cancer - Tong, Yu; Yu, Tao; Li, Shiping; Zhao, Fengyan; Ying, Junjie; Qu, Yi; Mu, Dezhi (Frontiers in Physiology, 2018)
Multiple independent cancer susceptibility loci at chromosome 8q24 have been identified by GWAS (Genome-wide association studies). Forty six articles including 60,293 cases and 62,971 controls were collected to conduct a meta-analysis to evaluate the associations between 21 variants in 8q24 and prostate cancer risk . Of the 21 variants located in 8q24, 15 were significantly associated with the risk of prostate cancer. In particular, both homozygous AA and heterozygous CA genotypes of rs16901979, as well as the AA and CA genotypes of rs1447295, were associated with the risk of prostate cancer. Our study showed that variants in the 8q24 region are associated with prostate cancer risk in this large-scale research synopsis and meta-analysis. Further studies are needed to explore the role of the 8q24 variants involved in the etiology of prostate cancer.